Changes in Depression Levels in the Elderly With a Spiritual Approach And Deep Breathing Relaxation At UPT PSTW Blitar In Tulungagung - Lenni Agusti Wijayanti; Dinda Deristia; Catur Wahyu Febriani; Hiromi Ogasawara (Open Access Health Scientific Journal, 2022)
Background: Psychological changes in the elderly include feelings of loneliness, fear of loss, fear of death, anxiety, useless feeling, dependence and neglect and depression. This study aimed to determine the effect of a spiritual approach and deep breathing relaxation on changes in the level of depression in the elderly.Methods: The design of this study was a Pre-Experimental, One-group pre-post test design with a population of all elderly people at the Tresna Werdha Blitar Social Services UPT with a total of 80 respondents. The sample is part of the population with a purposive sampling technique of 40 respondents. The data that has been collected is processed by the Wilcoxon Match Pairs Test statistical test with a significance of = 0.05.Results: The results of the analysis of the Wilcoxon Match Pairs Test obtained a p-value = 0.000 which is less than the value of (0.05), it can be concluded that H0 is rejected, meaning that there is an influence of spiritual approach and deep breath relaxation on changes in depression levels in the elderly.Conclusion: Spiritual approach therapy and deep breathing relaxation are effective in overcoming depression in the elderly, so this needs to be done continuously, in collaboration with the local health center and involving the participation of nursing home staff